A diagnostic approach to syndromic retinal dystrophies with intellectual disability. Issue 3 (11th September 2020) - Yang, Xiao‐Ru; Benson, Matthew D.; MacDonald, Ian M.; Innes, A. Micheil
Abstract: Inherited retinal dystrophies are a group of monogenic disorders that, as a whole, contribute significantly to the burden of ocular disease in both pediatric and adult patients. In their syndromic forms, retinal dystrophies can be observed in association with intellectual disability, frequently alongside other systemic manifestations. There are now over 80 genes implicated in syndromic retinal dystrophies with intellectual disability. Identifying and accurately characterizing these disorders allows the clinician to narrow the differential diagnosis, evaluate for relevant associated features, arrive at a timely and accurate diagnosis, and address both sight‐threatening ocular manifestations and morbidity‐causing systemic manifestations. The co‐occurrence of retinal dystrophy and intellectual disability in an individual can be challenging to investigate, diagnose, and counsel given the considerable phenotypic and genotypic heterogeneity that exists within this broad group of disorders. We performed a review of the current literature and propose an algorithm to facilitate the evaluation, and clinical and mechanistic classification, of these individuals.